Double-pore-size distribution zirconium oxide capillary core for loop heat pipe and preparation method of double-pore-size distribution zirconium oxide capillary core

By designing a double-pore structure and optimization process in the zirconia capillary core, the problems of poor thermal conductivity and complex processing of traditional metal capillary cores are solved, and capillary cores with high porosity and low thermal conductivity are achieved, which significantly improves the loop heat pipe Stability and heat dissipation performance.

CN119320274AActive Publication Date: 2025-01-17SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411321709.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-17
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The traditional metal capillary core has poor thermal conductivity and heat leakage problems in the loop heat pipes, and is complicated to process, making it difficult to meet the heat dissipation needs of high-heat flow density electronic equipment.

Method used

Using a double-pore-distributed zirconia capillary core, the pore-forming agent and foaming agent are added to the zirconia slurry, and the large pore and small pore structure is formed. Combined with the optimization of the sintering process, high pores are prepared. Capillary core with low thermal conductivity.

Benefits of technology

It significantly improves the stability and reliability of the loop heat pipe, reduces the flow resistance of the working fluid, avoids the micropore closure problem of the metal capillary core, and achieves efficient heat transfer and heat dissipation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320274A_ABST
    Figure CN119320274A_ABST
Patent Text Reader

Abstract

The invention relates to a double-pore-size distribution zirconium oxide capillary core for a loop heat pipe and a preparation method of the double-pore-size distribution zirconium oxide capillary core. The preparation method of the double-pore-size distribution zirconium oxide capillary core for the loop heat pipe comprises the following steps: (1) preparing zirconium oxide slurry containing a pore forming agent; the average particle size of the pore-forming agent is 1-20 microns, and the addition amount of the pore-forming agent accounts for 15-30 wt% of the mass of the zirconium oxide; (2) adding a foaming agent into the zirconium oxide slurry, and mechanically stirring and foaming to obtain foam slurry; the adding amount of the foaming agent accounts for 0.01-1wt% of the mass of zirconium oxide; (3) the foam slurry is injected into a mold and dried, and a capillary core green body is obtained; and (4) sintering the capillary core green body, and processing to obtain the double-pore-size distribution zirconium oxide capillary core for the loop heat pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of porous medium phase change and flow material, and specifically relates to a double-aperture distribution zirconium oxide capillary wick for a loop heat pipe and a preparation method thereof, which can be applied to the fields of heat dissipation of portable or desktop computers and other high heat flux density electronic devices. Background Art

[0002] As modern electronic devices develop towards lightweight, miniaturization and high performance, traditional air cooling technology can no longer meet the heat dissipation needs of electronic components with high heat flux density in a limited space. As a passive two-phase heat transfer device, the loop heat pipe has a separate circulation of gas and liquid phases, which avoids the hedging effect between the gas and liquid phases of traditional heat pipes and realizes the long-distance transmission of heat. It has the advantages of strong heat transfer capacity, no moving parts, long transmission distance, and flexible space arrangement. It has good application prospects in the heat dissipation of high heat flux density electronic equipment.

[0003] As the core component of the loop heat pipe evaporator, the capillary wick can provide capillary driving force to ensure the normal vapor-liquid circulation in the loop, prevent heat leakage and structural phase change, etc. At present, the commonly used metal capillary wicks have a high effective thermal conductivity, and the heat leakage from the evaporator to the liquid reservoir is large, which is not conducive to the startup and stable operation of the loop heat pipe; at the same time, the micropores on the outer surface of the capillary wick are prone to closure during the processing of the metal capillary wick, affecting the thermal performance of the product. On the other hand, the capillary wick used in the loop heat pipe requires a strong capillary driving force to circulate the working fluid, and also needs to reduce the flow resistance of the working fluid inside it, and transfer the generated steam to the steam pipe in time.

[0004] Ceramics can be used as an excellent candidate material for capillary wicks. However, the traditional ceramic powder pressing process can only produce some capillary wick products with simple shapes, and the processing technology is complicated. Therefore, it is particularly important to improve the performance of capillary wicks for loop heat pipes by improving the material, designing the pore structure and optimizing the process. Summary of the invention

[0005] In view of the above technical problems, the object of the present invention is to provide a double pore size distribution zirconia capillary wick for a loop heat pipe with high strength, low thermal conductivity, high porosity and simple process and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing a double pore size distribution zirconium oxide capillary wick for a loop heat pipe, the preparation method comprising the following steps: (1) preparing a zirconium oxide slurry containing a pore-forming agent; the average particle size of the pore-forming agent is 1 to 20 μm, and the amount added accounts for 15 to 30 wt% of the mass of the zirconium oxide; (2) adding a foaming agent to the zirconium oxide slurry and mechanically stirring and foaming the slurry to obtain a foam slurry; the amount of the foaming agent added is 0.01 to 1 wt% of the mass of the zirconium oxide; (3) injecting the foam slurry into a mold and drying it to obtain a capillary wick green body; (4) Sintering the capillary core green body to obtain the double pore size distribution zirconia capillary core for the loop heat pipe after processing.

[0007] Preferably, in step (1), the pore-forming agent is at least one of starch, sawdust, carbon, polymethyl methacrylate, urea particles, phenolic resin, stearic acid particles, polystyrene, polyvinyl alcohol, and organic whiskers.

[0008] Preferably, in step (1), the zirconia slurry further comprises a dispersant accounting for 0.1 to 5 wt% of the mass of the zirconia powder and a gelling agent accounting for 0.1 to 3 wt% of the mass of the zirconia powder, and the solid content of the zirconia slurry is 10 to 50 vol%; Preferably, the dispersant is at least one of polyethylene glycol, polycarboxylate, polyacrylate, lactic acid, and lignin sulfonate, and the gelling agent is isobutylene-maleic anhydride copolymer.

[0009] Preferably, in step (2), the foaming agent is a cationic surfactant; preferably at least one of dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecylhydroxyethyldimethylammonium bromide and hexadecyltrimethylammonium bromide.

[0010] Preferably, in step (2), the mechanical stirring foaming process is ball milling stirring at a rotation speed of 100 to 500 rpm for 0.5 to 5 hours.

[0011] Preferably, in step (4), the sintering process is as follows: firstly heating to 500-900°C at a rate of 1-5°C / min and then keeping the temperature for 1-4 hours, then heating to 1200-1600°C at a rate of 2-10°C / min and then keeping the temperature for 1-10 hours.

[0012] Preferably, in step (4), the processing is mechanical processing, and the processing accuracy is 10 to 100 μm in roundness and 10 to 100 μm in straightness.

[0013] In the second aspect, the present invention provides a double pore size distribution zirconia capillary wick for a loop heat pipe obtained according to the above-mentioned preparation method, wherein the double pore size distribution zirconia capillary wick for a loop heat pipe has both small pores left after the pyrolysis of the pore-forming agent and large pores left by the bubbles produced by foaming, wherein the small pores are located on the pore walls of the large pores and the large pores and the small pores are interconnected.

[0014] Preferably, the open porosity of the double pore size distribution zirconia capillary core for the loop heat pipe is 60-90%; preferably, the average pore size of the macropores is 30-500 μm, and the volume fraction is 65-80%; the average pore size of the small pores in the macropore wall is 0.1-20 μm, and the volume fraction is 0.5-10%.

[0015] Preferably, the double-aperture-distributed zirconium oxide capillary wick used in the loop heat pipe has a compressive strength of 1 to 60 MPa and a thermal conductivity of 0.1 to 0.5 W (m / K).

[0016] Beneficial Effects (1) The present invention selects zirconia ceramics with high brittleness, good chemical stability and low thermal conductivity as the capillary wick material, which can avoid the problem that the surface micropores of the metal material capillary wick are easily closed after processing, improve the compatibility of the capillary wick with the working fluid, and reduce the reverse heat leakage from the evaporator to the liquid reservoir, thereby significantly improving the stability and reliability of the loop heat pipe; (2) The dual-aperture distribution zirconium oxide capillary core provided by the present invention has large pores and small pores in the same space. The small pores formed by the pore-forming agent provide the capillary core with sufficient capillary suction force and provide an attachment surface for the phase change interface, thereby stabilizing the phase change interface. The large pores formed by the bubbles can reduce the flow resistance of the working fluid and can also effectively reduce the size of the capillary core when used. (3) The present invention can control the pore size and open porosity of the double pore size distribution zirconia capillary wick by selecting zirconia powder with different addition ratios and pore formers with different particle sizes and different addition ratios; (4) The capillary core sintered green body of the present invention is cast into a mold, which can achieve near-net-shape molding of the capillary core product and reduce the preparation and processing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a process flow chart of preparing a double-pore-size-distributed zirconium oxide capillary wick for a loop heat pipe according to an example of the present invention; Figure 2 This is a physical picture of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe prepared in Example 1; Figure 3-5 They are scanning electron microscope images of the double pore size distribution zirconium oxide capillary core prepared in Examples 1-3 respectively; Figure 6 , 7 The scanning electron microscope images of the double pore size distribution zirconia capillary wick for loop heat pipe prepared in Examples 4 and 5 respectively; Figure 8 This is a scanning electron microscope image of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe prepared in Example 6; Fig. 9 This is a scanning electron microscope image of the zirconium oxide capillary core prepared in Comparative Example 1. DETAILED DESCRIPTION

[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0019] The following, combined Figure 1 , exemplarily illustrating the preparation method of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe provided by the present invention. The preparation method may include the following steps: (1) adding a dispersant, a gelling agent, a pore-forming agent, and zirconium oxide powder into water and mixing them to obtain a zirconium oxide slurry; (2) adding a foaming agent to the zirconium oxide slurry and performing mechanical stirring and foaming to obtain a foam slurry; (3) injecting the foam slurry into a mold and drying it to obtain a capillary wick green body; (4) Sintering the capillary wick green body and then processing it to obtain the double pore size distribution zirconia capillary wick for the loop heat pipe.

[0020] In some embodiments, in step (1), the dispersant may be at least one of polyethylene glycol, polycarboxylate, polyacrylate, lactic acid, and lignin sulfonate; the amount of the dispersant added may account for 0.1 to 5 wt% of the mass of the zirconium oxide powder. The pore-forming agent can be uniformly dispersed in the zirconium oxide slurry by adding the dispersant. If the dispersant content is too high, the slurry viscosity will be too low, reducing the stability of the foam slurry; if the content is too low, the slurry viscosity will increase, the dispersion effect will deteriorate, and the foaming will be insufficient or difficult to foam during the subsequent mechanical stirring foaming process.

[0021] In some embodiments, in step (1), the gelling agent may be an isobutylene-maleic anhydride copolymer; the amount of the gelling agent added may account for 0.1 to 3 wt % of the mass of the zirconium oxide powder. The present invention uses a novel water-based gelling agent, isobutylene-maleic anhydride copolymer, as a gelling agent, which can increase the stability of the foam slurry, reduce bubble rupture during the drying process of the foam slurry, and increase the yield. However, if too much gelling agent is added, the viscosity of the zirconium oxide slurry will be too high, resulting in insufficient or even difficult foaming.

[0022] In some embodiments, in step (1), the pore-forming agent may be at least one of starch, sawdust, carbon, polymethyl methacrylate, urea particles, phenolic resin, stearic acid particles, polystyrene, polyvinyl alcohol, and organic whiskers; the average particle size of the pore-forming agent may be 1 to 20 μm, and the added amount may account for 15 to 30 wt% of the mass of the zirconium oxide powder.

[0023] Among them, in order to ensure the smooth progress of mechanical stirring foaming and the strength of the green body after pyrolysis of the pore-forming agent, if the particle size of the pore-forming agent is too large, the small holes left after pyrolysis of the pore-forming agent during the sintering process will be too large, reducing the strength of the capillary wick sintered green body, and further causing the green body to pulverize; if the particle size of the pore-forming agent is too small, the attraction between the pore-forming agents in the zirconia slurry will increase, and the viscosity of the zirconia slurry will increase, which will make the foaming insufficient or difficult to foam.

[0024] Furthermore, if the amount of pore-forming agent added is insufficient, the gas generated by the pyrolysis of the pore-forming agent during the subsequent sintering process will be difficult to discharge from the capillary wick sintered green body, causing the green body to crack; if the amount of pore-forming agent added is too much, too many small pores will be left after the pyrolysis of the pore-forming agent during the sintering process, reducing the strength of the capillary wick sintered green body and easily causing the green body to pulverize.

[0025] In some embodiments, in step (1), the mixing process can be ball milling stirring at a rotation speed of 50 to 400 rpm for 1 to 10 hours.

[0026] In some embodiments, in step (1), the amount of water added may be 20 to 300 wt% of the mass of the zirconium oxide powder, and the solid content of the zirconium oxide slurry may be controlled to be 10 to 50 vol%.

[0027] The open porosity of the dual-aperture distribution zirconia capillary core can be regulated by adjusting the solid content, so the solid content range should be increased as much as possible to a certain extent. However, too high or too low solid content is not conducive to the preparation of the capillary core: when the solid content is too high, the slurry loses fluidity, making it difficult to disperse the pore-forming agent and mechanically stir and foam; when the solid content is too low, the slurry viscosity is too low, and the bubbles introduced during the mechanical stirring and foaming process are difficult to stabilize, making it impossible to prepare the foam slurry.

[0028] In some embodiments, in step (2), the foaming agent can be a cationic surfactant, preferably at least one of dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecylhydroxyethyldimethylammonium bromide, and hexadecyltrimethylammonium bromide; the amount of the foaming agent added can account for 0.01 to 1 wt% of the mass of the zirconium oxide powder.

[0029] The present invention uses a cationic surfactant as a foaming agent. The cationic surfactant is adsorbed on the surface of zirconium oxide particles with full surface charge under the action of electrostatics to achieve the effect of hydrophobic modification. During the mechanical stirring and foaming process, the zirconium oxide particles with hydrophobic surface modification are irreversibly adsorbed on the gas-liquid interface to stabilize the bubbles.

[0030] In some embodiments, in step (2), the mechanical stirring foaming process can be ball milling stirring at a rotation speed of 100 to 500 rpm for 0.5 to 5 hours.

[0031] The present invention uses a preparation process combining the addition of a pore-forming agent and direct foaming to prepare a porous zirconia capillary wick with a double pore size distribution having both large pores and small pores. The small pores formed by the pore-forming agent enable the capillary wick to have sufficient capillary suction force, and at the same time provide an adhesion surface for the phase change interface, thereby stabilizing the phase change interface. The large pores formed by the bubbles can reduce the flow resistance of the working fluid, and can also effectively reduce the size of the capillary wick when used, thereby effectively promoting the improvement of the performance of the capillary wick for the loop heat pipe.

[0032] In some embodiments, in step (3), the drying temperature may be 25 to 45° C. and the drying time may be 24 to 72 hours.

[0033] In some embodiments, in step (4), the sintering system can be: first heating to 500-900°C at a rate of 1-5°C / min and then keeping warm for 1-4 hours, then heating to 1200-1600°C at a rate of 2-10°C / min and then keeping warm for 1-10 hours.

[0034] The purpose of the present invention using two stages of heating with different heating rates is to control the pyrolysis rate of the pore-forming agent and avoid the release of gas due to too fast pyrolysis to damage the capillary wick green body. If the heating rate in the first stage is too fast, the green body is easily pulverized under the impact of the gas. If the heating rate in the second stage is too fast, the green body sintering shrinkage is too fast, which is easy to cause the green body to crack; if the heating rate at the second end is too slow, the sintering time will increase and the cost will increase. At the same time, if the sintering temperature is too low, the zirconium oxide particles in the green body cannot be completely sintered, affecting the strength of the capillary wick; if the sintering temperature is too high, the shrinkage of the green body will increase and the porosity of the capillary wick will be reduced. In addition, if the holding time is too short, the zirconium oxide particles will not be completely consolidated; if the holding time is too long, the sintering time will increase and the cost will increase.

[0035] In some embodiments, in step (4), the processing is mechanical processing, and the processing accuracy can be 10 to 100 μm in roundness and 10 to 100 μm in straightness.

[0036] In summary, the technical solution disclosed in the present invention overcomes the two major technical difficulties of the stability of zirconia foam slurry and the influence of pore-forming agent pyrolysis on green body strength during sintering. On the one hand, the present invention uses cationic foaming agent and novel water-based gelling agent isobutylene-maleic anhydride copolymer as gelling agent to stabilize zirconia foam slurry, avoiding unstable processes such as foam rupture, merging and Oswald ripening during the drying process of the foam slurry; on the other hand, the present invention controls the content and particle size of the pore-forming agent to ensure the smooth release of gas during sintering and the strength of the green body after pyrolysis. At the same time, the appropriate heating rate in the sintering step also helps to control the pyrolysis rate of the pore-forming agent, avoiding the green body structure from being damaged by gas impact under rapid pyrolysis. The present invention designs the sintering system based on the principle of reducing the damage of the pore-forming agent pyrolysis to the green body strength. Before ensuring the temperature at which the pore-forming agent can be completely pyrolyzed, a slow heating rate is used, and then the temperature is kept for a period of time to ensure that the pore-forming agent is completely pyrolyzed, and then a faster heating rate is used to reduce the sintering time. After reaching the general sintering temperature of zirconia, it is kept for a period of time to ensure the consolidation of zirconia. The sintering system of the present invention avoids the destruction of the green body and completes the consolidation of the zirconium oxide powder, thereby ensuring the smooth generation of the double-aperture structure.

[0037] The present invention adopts the method of combining the addition of pore-forming agent and direct foaming to prepare a dual-pore size distribution zirconia capillary core for the first time. The dual-pore size distribution refers to the presence of small pores left after the pore-forming agent is pyrolyzed and large pores left by bubbles generated by mechanical stirring and foaming in the zirconia capillary core. The pore size and volume fraction of large and small pores of the dual-pore size distribution zirconia capillary core prepared by the method of the present invention can be controlled by adjusting the raw material ratio. The present invention introduces an appropriate number of small pores into the pore walls of the large pores so that the large pores are interconnected.

[0038] The present invention uses a combination of adding a pore-forming agent and direct foaming to prepare a zirconia capillary wick with a large and small pore structure, which can simultaneously improve the capillary force and reduce the flow resistance; and, by selecting zirconia ceramics with high brittleness, good chemical stability and low thermal conductivity as the capillary wick material, the closure of surface micropores after the capillary wick is processed can be avoided, the compatibility of the capillary wick with the working fluid can be improved, the reverse heat leakage from the evaporator to the liquid storage device can be reduced, and the stability and reliability of the loop heat pipe can be significantly improved.

[0039] It should be noted that the technical solution disclosed in the present invention is not applicable to the preparation of silicon oxide materials. The main reason is that the surface properties of silicon oxide are different from those of zirconium oxide. After foaming with a cationic foaming agent, the foam slurry is difficult to gel and is prone to unstable processes such as foam rupture, merging and Oswald ripening.

[0040] The open porosity is calculated by the Archimedean drainage method, the microstructure is observed by a scanning electron microscope, and the compressive strength is tested by a universal mechanical testing machine. The open porosity of the double-pore-size distribution zirconia capillary wick for the loop heat pipe obtained by the above preparation method is 60-90%; preferably, the average pore size of the macropores is 30-500 μm, and the volume fraction is 65-80%; the average pore size of the small pores in the macropore wall is 0.1-20 μm, and the volume fraction is 0.5-10%; the compressive strength is 1-60 MPa; and the thermal conductivity is 0.1-0.5 W (m / K).

[0041] The large pores inside the dual-aperture distribution zirconia capillary core provided by the present invention are interconnected through small pores. During the working fluid transfer process in the capillary core, the working fluid flows alternately in the large and small pores. The working fluid in each large pore is a collection of multiple small pore working fluids. The liquid with a faster flow rate in the small pores will drag the fluid in the large pores, and finally the flow rate in the small pore cluster part reaches a uniform average value. The proportion of large and small pore clusters in the capillary core can be controlled by controlling the addition ratio of zirconia powder and pore-forming agent.

[0042] The dual pore size distribution zirconia capillary wick of the present invention has the characteristics of high strength, low thermal conductivity, high porosity and simple process. At the same time, its pore structure is a dual pore size distribution including large pores and small pores, which can improve capillary force and reduce flow resistance. Zirconia ceramics with good chemical stability and low thermal conductivity are used as capillary wicks to avoid the closure of surface micropores after processing, improve the compatibility of the working fluid, and reduce the reverse heat leakage from the evaporator to the liquid storage tank, thereby significantly improving the stability and reliability of the loop heat pipe.

[0043] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0044] Example 1

[0045] The preparation method of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe provided in this embodiment comprises the following steps: (1) adding a dispersant polyethylene glycol, a gelling agent isobutylene-maleic anhydride copolymer, a pore-forming agent polymethyl methacrylate, and zirconium oxide powder to water, and ball milling at a speed of 300 rpm for 3 hours to obtain a zirconium oxide slurry; the mass ratio of the polyethylene glycol, isobutylene-maleic anhydride copolymer, polymethyl methacrylate, zirconium oxide powder and water is 0.8:0.5:18:100:94, and the particle size of polymethyl methacrylate is 15 μm; (2) adding 0.1 wt% of cetyltrimethylammonium bromide based on the weight of zirconium oxide powder to the above zirconium oxide slurry, stirring and foaming the mixture at 400 rpm for 1 h using a planetary ball mill to obtain a foam slurry; (3) pouring the foam slurry into a mold and drying it at 25° C. for 72 hours to obtain a capillary core green body; (4) The capillary core green body is first heated to 600°C at a heating rate of 1°C / min and kept at this temperature for 2 hours, then heated to 1500°C at a heating rate of 3°C / min and kept at this temperature for 2 hours for sintering, and then mechanically processed with a roundness of 20 μm and a straightness of 50 μm to obtain the double-aperture distribution zirconia capillary core for the loop heat pipe.

[0046] Figure 2 This is a real picture of the double pore size distribution zirconium oxide capillary core for the loop heat pipe prepared in Example 1. It can be seen from the figure that the surface of the capillary core is smooth without defects such as cracks and notches.

[0047] Example 2

[0048] The preparation process of the dual pore size distribution zirconium oxide capillary wick for loop heat pipe in this Example 2 refers to that in Example 1, the main difference is that in step (1), the amount of pore-forming agent polymethyl methacrylate added is 21wt% of the mass of zirconium oxide powder.

[0049] Example 3

[0050] The preparation process of the dual pore size distribution zirconium oxide capillary wick for loop heat pipe in this Example 3 refers to that in Example 1, the main difference is that in step (1), the amount of pore-forming agent polymethyl methacrylate added is 24wt% of the mass of zirconium oxide powder.

[0051] Figure 3-5 The scanning electron microscope images of the double pore size distribution zirconia capillary core prepared in Examples 1 to 3 are shown respectively. It can be seen from the figure that the zirconia capillary core obtained by the preparation process provided by the present invention has a double pore size distribution structure, and as the amount of pore-forming agent polymethyl methacrylate added increases, the number of small pores in the macropore wall increases.

[0052] Example 4

[0053] The preparation process of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe in this Example 4 refers to that in Example 1, the main difference is that in step (1), the particle size of the pore-forming agent polymethyl methacrylate added to the slurry is 10 μm.

[0054] Example 5

[0055] The preparation process of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe in this Example 5 refers to that in Example 1, with the main difference being that in step (1), the particle size of the pore-forming agent polymethyl methacrylate added to the slurry is 3 μm.

[0056] Figure 6 , 7 The scanning electron microscope images of the double pore size distribution zirconium oxide capillary wick for loop heat pipe prepared in Examples 4 and 5 are shown respectively. It can be seen from the image that as the particle size of the pore-forming agent polymethyl methacrylate decreases, the number of small pores in the macropore wall increases and the pore size decreases.

[0057] Example 6

[0058] The preparation process of the dual pore size distribution zirconium oxide capillary wick for the loop heat pipe in Example 6 refers to Example 1, with the main difference being that the mass ratio of the added polyethylene glycol, isobutylene-maleic anhydride copolymer, polymethyl methacrylate, zirconium oxide powder and water is 0.8:0.5:18:100:50.

[0059] Figure 8 This is a scanning electron microscope image of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe prepared in Example 6. Figure 3 It can be seen that the zirconia capillary wick prepared with a relatively higher solid content zirconia slurry has a smaller macropore size.

[0060] Comparative Example 1

[0061] The preparation process of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe in this comparative example 1 refers to that in Example 1, the main difference is that in step (1), the pore-forming agent polymethyl methacrylate is not added.

[0062] Fig. 9 This is a scanning electron microscope image of the zirconia capillary core prepared in Comparative Example 1. As can be seen from the image, the zirconia capillary core prepared in Comparative Example 1 has only macropores left by bubbles, and the macropores are separated by complete pore walls, presenting a single pore size distribution structure.

[0063] Comparative Example 2

[0064] The preparation process of the double pore size distribution zirconium oxide capillary wick for loop heat pipe in Comparative Example 2 refers to Example 1, with the main difference that in step (1), the amount of pore-forming agent polymethyl methacrylate added is 35wt% of the mass of zirconium oxide powder.

[0065] The test shows that when too much polymethyl methacrylate is added, the pore structure of the capillary wick sintered green body collapses during the sintering process. The reason is that the small pores left after the pore-forming agent is pyrolyzed reduce the strength of the capillary wick sintered green body.

[0066] Comparative Example 3

[0067] The preparation process of the double pore size distribution zirconium oxide capillary wick for loop heat pipe in this comparative example 3 refers to that in Example 1, the main difference is that in step (1), the amount of pore-forming agent polymethyl methacrylate added is 8wt% of the mass of zirconium oxide powder.

[0068] The test shows that when insufficient polymethyl methacrylate is added, the capillary wick sintered green body will crack during the sintering process. The reason is that the gas generated by the thermal decomposition of the pore-forming agent during the sintering process is difficult to be discharged from the capillary wick sintered green body.

[0069] Comparative Example 4

[0070] The preparation process of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe in Comparative Example 4 refers to that in Example 1, with the main difference being that in step (1), the particle size of the pore-forming agent polymethyl methacrylate added to the slurry is 50 μm.

[0071] The test shows that when the particle size of the added polymethyl methacrylate is too large, the pore structure of the capillary wick sintered green body collapses during the sintering process. The reason is that the pore size of the small holes left after the pore-forming agent is pyrolyzed increases, which reduces the strength of the capillary wick sintered green body.

[0072] Comparative Example 5

[0073] The preparation process of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe in this comparative example 5 refers to that in Example 1, the main difference is that in step (1), the particle size of the pore-forming agent polymethyl methacrylate added to the slurry is 0.8 μm.

[0074] Tests have shown that when the particle size of the added polymethyl methacrylate is too small, the attraction between the pore-forming agents in the zirconia slurry increases, and the viscosity of the zirconia slurry increases, making it difficult to foam to obtain a foam slurry.

[0075] Comparative Example 6

[0076] The preparation process of the double pore size distribution zirconium oxide capillary wick for the loop heat pipe in this comparative example 6 refers to that in Example 1, with the main difference being that in step (4), the capillary wick green body is first heated to 600°C at a heating rate of 6°C / min and kept at that temperature for 2h, and then heated to 1500°C at a heating rate of 3°C / min and kept at that temperature for 2h for sintering.

[0077] The test shows that the capillary wick green body is pulverized under the impact of the gas generated by the pyrolysis of polymethyl methacrylate due to the excessively fast initial heating rate.

[0078] Table 1 below shows the performance parameters of the zirconium oxide capillary wicks prepared in various embodiments and comparative examples of the present invention:

[0079] It can be seen from Table 1 that the open porosity, pore size and volume fraction of large and small pores, and strength of the dual pore size distribution zirconia capillary wick prepared by the method of the present invention can be controlled by adjusting the raw material ratio.

[0080] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a double pore size distribution zirconium oxide capillary wick for a loop heat pipe, characterized in that: The preparation method comprises the following steps: (1) preparing a zirconium oxide slurry containing a pore-forming agent; the average particle size of the pore-forming agent is 1 to 20 μm, and the amount added accounts for 15 to 30 wt% of the mass of the zirconium oxide; (2) adding a foaming agent to the zirconium oxide slurry and mechanically stirring and foaming the slurry to obtain a foam slurry; the amount of the foaming agent added is 0.01 to 1 wt% of the mass of the zirconium oxide; (3) injecting the foam slurry into a mold and drying it to obtain a capillary wick green body; (4) Sintering the capillary core green body to obtain the double pore size distribution zirconia capillary core for the loop heat pipe after processing.

2. The preparation method according to claim 1, characterized in that: In step (1), the pore-forming agent is at least one of starch, sawdust, carbon, polymethyl methacrylate, urea particles, phenolic resin, stearic acid particles, polystyrene, polyvinyl alcohol, and organic whiskers.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the zirconia slurry further comprises a dispersant accounting for 0.1 to 5 wt% of the mass of the zirconia powder and a gelling agent accounting for 0.1 to 3 wt% of the mass of the zirconia powder, and the solid content of the zirconia slurry is 10 to 50 vol%; Preferably, the dispersant is at least one of polyethylene glycol, polycarboxylate, polyacrylate, lactic acid, and lignin sulfonate, and the gelling agent is isobutylene-maleic anhydride copolymer.

4. The preparation method according to any one of claims 1 to 3, characterized in that In step (2), the foaming agent is a cationic surfactant; preferably at least one of dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecylhydroxyethyldimethylammonium bromide and hexadecyltrimethylammonium bromide.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), the mechanical stirring foaming process is ball milling stirring at a rotation speed of 100 to 500 rpm for 0.5 to 5 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (4), the sintering system is: firstly heating to 500-900°C at a rate of 1-5°C / min and then keeping the temperature for 1-4 hours, then heating to 1200-1600°C at a rate of 2-10°C / min and then keeping the temperature for 1-10 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (4), the processing is mechanical processing, and the processing accuracy is 10 to 100 μm in roundness and 10 to 100 μm in straightness.

8. A double pore size distribution zirconium oxide capillary wick for a loop heat pipe obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The loop heat pipe uses a dual-aperture distribution zirconium oxide capillary core, which has both small pores left after the pore-forming agent is pyrolyzed and large pores left by bubbles generated by foaming. The small pores are located on the pore walls of the large pores, and the large pores and the small pores are interconnected.

9. The double pore size distribution zirconia capillary wick for loop heat pipe according to claim 8, characterized in that: The open porosity of the double pore size distribution zirconia capillary wick for the loop heat pipe is 60-90%; preferably, the average pore size of the macropores is 30-500 μm, and the volume fraction is 65-80%; the average pore size of the small pores in the macropore wall is 0.1-20 μm, and the volume fraction is 0.5-10%.

10. The double pore size distribution zirconia capillary wick for loop heat pipe according to claim 8 or 9, characterized in that: The double-aperture distribution zirconium oxide capillary core used in the loop heat pipe has a compressive strength of 1-60 MPa and a thermal conductivity of 0.1-0.5 W (m / K).

Citation Information

Patent Citations

  • Method for preparing closed pore foam ceramic

    CN101955371A

  • Zirconia fiber-reinforced alumina closed-cell foam ceramic and preparation method thereof

    CN105481355A

  • Ultralight three-dimensional hierarchical porous cerium dioxide material and preparation method thereof

    CN112850776A

  • Preparation method of high-strength open-cell zirconium oxide foamed ceramic

    CN115160017A

  • Iron tailing-based soil improvement material and preparation method thereof

    CN116768649A